The Effect of Adaptive User Interfaces on Task Completion Time in Mobile Health Applications for Elderly Users in Rwanda - Kanakuze, Judith (International Journal of Computing and Engineering, 2025)
Purpose: The purpose of this article was to analyze effect of adaptive user interfaces on task completion time in mobile health applications for elderly users in Rwanda. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Studies show adaptive user interfaces in mobile health apps help elderly users in Rwanda complete tasks up to 35% faster by adjusting features like font size and navigation. While some users needed time to adapt, overall efficiency and usability improved significantly. Unique Contribution to Theory, Practice and Policy: Technology acceptance model (TAM), cognitive load theory (CLT) & unified theory of acceptance and use of technology (UTAUT) may be used to anchor future studies on the effect of adaptive user interfaces on task completion time in mobile health applications for elderly users in Rwanda. Designers and developers of mobile health applications should prioritize implementing adaptive interface features such as dynamic font scaling, simplified navigation paths, and personalized feedback mechanisms that adjust to users’ evolving needs and abilities. Policymakers should establish clear accessibility standards and regulatory guidelines that mandate the inclusion of adaptive interface requirements in all certified mobile health applications targeting older populations.